Shankopathies in the Developing Brain in Autism Spectrum Disorders - Vyas, Yukti; Cheyne, Juliette E.; Lee, Kevin; Jung, Yewon; Cheung, Pang Ying; Montgomery, Johanna M. (Frontiers in Neuroscience, 2021)
The SHANK family of proteins play critical structural and functional roles in the postsynaptic density (PSD) at excitatory glutamatergic synapses. Through their multidomain structure they form a structural platform across the PSD for protein–protein interactions, as well as recruiting protein complexes to strengthen excitatory synaptic transmission. Mutations in SHANKs reflect their importance to synapse development and plasticity. This is evident in autism spectrum disorder (ASD), a neurodevelopmental disorder resulting in behavioural changes including repetitive behaviours, lack of sociability, sensory issues, learning, and language impairments. Human genetic studies have revealed ASD mutations commonly occur in SHANKs. Rodent models expressing these mutations display ASD behavioural impairments, and a subset of these deficits are rescued by reintroduction of Shank in adult animals, suggesting that lack of SHANK during key developmental periods can lead to permanent changes in the brain’s wiring. Here we explore the differences in synaptic function and plasticity from development onward in rodent Shank ASD models. To date the most explored brain regions, relate to the behavioural changes observed, e.g., the striatum, hippocampus, sensory, and prefrontal cortex. In addition, less-studied regions including the hypothalamus, cerebellum, and peripheral nervous system are also affected. Synaptic phenotypes include weakened but also strengthened synaptic function, with NMDA receptors commonly affected, as well as changes in the balance of excitation and inhibition especially in cortical brain circuits. The effects of shankopathies in activity-dependent brain wiring is an important target for therapeutic intervention. We therefore highlight areas of research consensus and identify remaining questions and challenges.